Genetic subtyping and phylogenetic analysis of HA and NA from avian influenza virus in wild birds from Peru reveals unique features among circulating strains in America - Castro-Sanguinetti, Gina R.; Marques Simas, Paulo Vitor; Apaza-Chiara, Ana Paola; Callupe-Leyva, Jose Alonso; Rondon-Espinoza, Juan Alexander; Gavidia, Cesar M.; More-Bayona, Juan Anderson; Gonzalez Veliz, Rosa Isabel; Vakharia, Vikram N.; Icochea, Maria Eliana (PLOS ONE, 2022)
Avian influenza virus (AIV) represents a major concern with productive implications in poultry systems but it is also a zoonotic agent that possesses an intrinsic pandemic risk. AIV is an enveloped, negative-sense and single-stranded RNA virus with a segmented genome. The eight genomic segments, comprising the whole genome, encode for eleven proteins. Within these proteins, Hemagglutinin (HA) and Neuraminidase (NA) are the most relevant for studies of evolution and pathogenesis considering their role in viral replication, and have also been used for classification purposes. Migratory birds are the main hosts and play a pivotal role in viral evolution and dissemination due to their migratory routes that comprise large regions worldwide. Altogether, viral and reservoir factors contribute to the emergence of avian influenza viruses with novel features and pathogenic potentials. The study aimed to conduct surveillance of AIVs in wild birds from Peru. A multi-site screening of feces of migratory birds was performed to isolate viruses and to characterize the whole genome sequences, especially the genes coding for HA and NA proteins. Four-hundred-twenty-one (421) fecal samples, collected between March 2019 and March 2020 in Lima, were obtained from 21 species of wild birds. From these, we isolated five AIV from whimbrel, kelp gull, Franklin’s gulls and Mallard, which were of low pathogenicity, including four subtypes as H6N8, H13N6, H6N2 and H2N6. Genetic analysis of HA and NA genes revealed novel features in these viruses and phylogenetic analysis exhibited a close relationship with those identified in North America (US and Canada). Furthermore, H2N6 isolate presented a NA sequence with higher genetic relationship to Chilean isolates. These results highlight that the geographical factor is of major relevance in the evolution of AIV, suggesting that AIV circulating in Peru might represent a new site for the emergence of reassortant AIVs.